2
Объяснение:
-2(3,5y - 2,5) + 4,5y - 1 = -7y + 5 +4,5y - 1 = 4 - 2,5y
4 - 2,5 • 4/5 = 4 - 2 = 2
2.
-2(3,5у - 2,5) + 4,5 - 1 = -2 х 3,5у - (-2) х 2,5 + 4,5у - 1 = -7у + 5 + 4,5у - 1 = -2,5у + 4
Если у = 4/5, то -2,5 х 4/5 + 4 = -20/10 + 5 = -2 + 4 = 2
2
Объяснение:
-2(3,5y - 2,5) + 4,5y - 1 = -7y + 5 +4,5y - 1 = 4 - 2,5y
4 - 2,5 • 4/5 = 4 - 2 = 2
2.
Объяснение:
-2(3,5у - 2,5) + 4,5 - 1 = -2 х 3,5у - (-2) х 2,5 + 4,5у - 1 = -7у + 5 + 4,5у - 1 = -2,5у + 4
Если у = 4/5, то -2,5 х 4/5 + 4 = -20/10 + 5 = -2 + 4 = 2